Ataxia–telangiectasia mutated kinase‐mediated upregulation of NKG2D ligands on leukemia cells by resveratrol results in enhanced natural killer cell susceptibility. Issue 6 (26th April 2013) - Luis Espinoza, J.; Takami, Akiyoshi; Trung, Ly Q.; Nakao, Shinji
<x xml:space="preserve">Abstract</x> The powerful activating receptor NKG2D is expressed by natural killer (NK) cells and promotes cytotoxic lysis of cancer cells expressing NKG2D ligands (NKG2D‐Ls). We report the effective induction of NKG2D‐Ls, achieved with the naturally occurring polyphenol resveratrol, in a broad range of leukemia cells. In this study, resveratrol upregulated the NKG2D‐Ls MHC class I chain‐related proteins MICA and MICB, and UL16‐binding proteins ULBP1, ULBP2, and ULBP3 in most of the leukemia cells analyzed. Ligand upregulation induced by resveratrol was impaired by pharmacological and genetic disruption of ataxia–telangiectasia mutated kinase, the main regulator of NKG2D‐L expression. Leukemia cells treated with resveratrol were more susceptible to killing by NK cells than untreated cells, and the enhanced cytotoxicity of NK cells was blocked by treatment of NK cells with anti‐NKG2D mAbs. Interestingly, resveratrol consistently upregulated the NKG2D receptor expression and enhanced NKG2D‐mediated functions in resting NK cells obtained from healthy individuals. Therefore, resveratrol has attractive immunotherapeutic potential.